A nonlinear correlation between the serum uric acid to creatinine ratio and the prevalence of hypertension: a large cross-sectional population-based study - Ru Wang; Shuxing Wu; Jing Wang; Wenting Li; Jian Cui; Zhuhua Yao (Renal Failure)
Objective To explore the relationship between the serum uric acid to creatinine (UA/Cr) ratio and the prevalence of hypertension.Methods In this cross-sectional study, we included 8571 individuals from the China Health and Nutrition Survey. Logistic regression analysis and restricted cubic spline (RCS) were used to analyze the relationship between the UA/Cr ratio and hypertension.Results Compared with individuals without hypertension, individuals with hypertension had higher UA/Cr ratios. Multivariate logistic regression analysis showed that a higher UA/Cr ratio was closely related to a higher risk of hypertension (as a continuous variable, OR: 1.054, 95% CI: 1.014-1.095, p = 0.007; as a categorical variable, Q3 vs. Q1, OR: 1.183, 95% CI: 1.011-1.384, p = 0.035; Q4 vs. Q1, OR: 1.347, 95% CI: 1.146-1.582, p < 0.001). Subgroup analysis revealed that the correlation between the UA/Cr ratio and hypertension risk was stable in all subgroups except for the subgroup with diabetes and the subgroup with a BMI ≥ 28 kg/m2 (p < 0.05). Sensitivity analysis confirmed the robustness of the relationship between a higher UA/Cr ratio and a higher risk of hypertension (p < 0.05). The RCS showed that the UA/Cr ratio was nonlinearly related to hypertension risk. Further threshold effect showed that only a UA/Cr ratio less than 5.0 was related to hypertension risk (OR: 1.178, 95% CI: 1.086-1.278, p < 0.001), and the 2-piecewise linear regression model was superior to the 1-line linear regression model (p < 0.05).Conclusion The UA/Cr ratio was associated with the prevalence of hypertension.